Fundamentals of Entrepreneurship ENT300: Dumpling Cassu / Nurul Ain Rajali... [et al.] - Rajali, Nurul Ain; Norman, Nurasila; Timbang, Nur Aqilah; Abd Karim, Azira Nabila; Ngataman, Ridzwan; Abdullah, Zul Amira (2015)
Dumpling Cassu is a start-up business that operated in Kuching, Sarawak. It is one of the business that being managed by bumiputera. The name of this business is come out from the imagination by the partnership members. It shows that how we positioning our products in customer's mind until they can remember our business name, simple and easy to pronounce. As for the business, we are providing a special, delicious dumpling and also beverages for the customers. As we go through with the changes of environment, people nowadays like to put on simple dishes on their own daily meals.